Atmospheric Acid Leaching Of Nickel-Copper Matte From Impala Platinum Refineries - R. M. Lamya (The Southern African Institute of Mining and Metallurgy, 2006)
The leaching behaviour of nickel?copper matte in an acidic?copper sulphate solution during the repulping stage at Impala Platinum Refineries has been studied. The base metal recovery process consists of a matte repulping stage prior to a series of pressure leach stages. Therefore, the repulping stage is basically an atmospheric leach stage in which the matte containing mostly Niand Cu is leached in copper-spent electrolyte from the tank house, resulting in dissolution of nickel and precipitation of almost all the copper. To understand the nature of the leaching process during this stage of the operation, the effects of temperature stirring rate and matte particle size on the rate and extent of base metal dissolution and copper rejection from the solution have been investigated. The leaching mechanism of the matte in the investigated system is alsoproposed.